A cidade e a política conforme a natureza - Perine, Marcelo (Universidad de Costa Rica, 2008)
The paper intends to settle a relationship of reciprocal elucidation between two surprising platonic utterances. The first one, in Republic (428 E), is "a city established on principles of nature" (kata physin oikistheisa polis); the second one, in the Statesman (308 D), speeks about a "the true natural art of statecraft" (kata physin alethos ousa politike). The comprehension of the two platonic formulas, in their contexts, allows to verify the coherence of the political thought of Plato in his late works.